Beyond the Porte de Saint-Denis: Looking inside the 10th arrondissement of Paris - Hasırcıoğlu, Ecem; Yıldırım, Galip Emre (Border Crossing, 2018)
Beyond the famous Porte de Saint-Denis, there is a “multiethnic” world, the Turks, the Kurds, the Arabs, the Indians, the Pakistanis cohabit and run their business in the same economic area. Despite the multi ethnical image, that district has a common reputation: “quartier turc”. In this purpose, this paper aims to present the presence of various social groups at the 10th arrondissement of Paris, particularly those who come from Turkey. The restaurants, the barbershops, the halal butcher shops or the grocery stores, placed side by side, show the diversity of the multiple forms of their economic integration. Turkish origin individuals who live and work at the 10th district, have different backgrounds, stories and reasons to settle down in Paris. In the light of this, we argue three types of migration from Turkey: first, work migration during the late 60’s; second, political refugees due to political context in the 80’s; and third cultural radiance (rayonnement culturel), as a new model, which encourages the educational and cultural mobilization of high skilled individuals. Each type of migration is related to the different models of the French migration policies. In this respect, we think that the field research based on the in-depth interviews will help us to discover their “migrant” universe. Focusing on a specific neighbor, known as “quartier turc”, this study attempts to analyze the migration stories, and the social, economic and political integration of those Turkish origin social groups at the 10th arrondissement of Paris.